Peningkatan Pengetahuan Tentang Hipertensi Pada Lansia di Posyandu Lansia Dukuh Gantungan Desa Makamhaji Kartasura Sukoharjo - Widyasari, Domas Fitria; Candrasari, Anika (Universitas Muhammadiyah Surakarta, 2010)
Hypertension is a degenerative disease that affects nearly 25% of the populationaround the world today and is a risk factor of cardiovascular disease. Geriatric(elderly) in Indonesia is a group of residents that become the focus of attention because of the number of elderly is increase, and brought variety of health problems.Hypertension can be treated with pharmacological treatment and lifestyle improvements with the correct knowledge based. Hypertension will be a problem ifelderly people are not guided and equipped with proper knowledge regarding thehealth of hypertension.SimakBaca secara fonetik The purpose of this activity is toimprove knowledge and attitudes about hypertension of rural elderly in GantunganMakamhaji Kartasura Sukoharjo. Health education about hypertension is given bylectures and discussion method. Evaluation used questionnaire that consist of 35questions, which was considered one if the answer is correct and zero if the answer is incorrect using pre-test and post-test about hypertension The results obtained bydescriptive mean. There is an increasing value of knowledge average abouthypertension after administration of education from 4.46 to 13.97 and attitudes average about hypertension from 3.49 to 9.90 Based on the result, health education institutions should cooperate with health service institutions to give information about hypertension through periodic health education. And government health institutions should expand health education focusing on elderly through Posyandu Lansia.